Los relatos de mujeres viajeras ¿Una mirada crítica sobre el colonialismo? Isabelle Eberhardt (1877-1904) - Garcia-Ramon, Maria Dolors; Mas, Abel Albet (Finisterra, 1998)
WOMEN'S TRAVEL NARRATIVES. A CRITICAL GAZE ON COLONIALISM? iSABELLE EBERHARDT (1877-1904) - The aim of this paper is to analyse the life and works of a woman travel writer, Isabelle Eberhardt and to set it within the context of the recent scholarship related to travel narrative, orientalism and gender. In effect, in his important work on orientalism, Said argued that the Orient is an European construct serving an image of the Other that not only defines the Other but also identifies the self as Western. Nevertheless, Said's contribution neglects the heterogenity of colonial discourse and conceals the roles played by women in the colonization process as well as in its representation. On the contrary, recent feminist scholarship focus on the role of European women as cultural agents in the formation of imperial relations and explores women's complicity with colonialism as well as their resistance to it. But most of the research on women travellers has been carried out by English-speaking authors on english-speaking women travellers. This paper, then, tries to contribute to this field by recovering a marginal voice coming from a different place:Isabelle Eberhardt was born in Geneva (although she was of Russian origin), travelled to Tunisia and Algeria and wrote in french. The complex dynamics of complicity and resistance in Western women is very clear in the case of Isabelle. On one hand, she has the reputation of being "an enemy of France" but, on the other, she is central to the colonial encounter. Isabelle transgresses European norms of gender and civilization by dressing as an Arab and embracing Islam, but her self-exploration was made possible by French colonial power, and in the end, she became a player in French imperial politics. The ambivalence towards colonialism that we can observe in Isabelle's life and works (as in many other women travellers) openly questions the notion of simple Otherness as presented in Said's work. The intersection of colonial and gender discourses involves a shifting subject positioning, whereby Western women can simultaneously constitute center and periphery, identity and alterity. Therefore, this paper hopefully shows that for the study of colonialism it is important to focus on narratives coming from the margins as they provide new perspectives which can destabilize established conceptions on the colonial relationship.